İlköğretim fen ve teknoloji dersi genetik ünitesinde öğretmen bilgilerinin "didaktiksel dönüşüm teorisi" yaklaşımıyla değerlendirilmesi. - (:unkn) unknown (My University, 2012)
Bu araştırma, ilköğretim 8. sınıf seviyesinde didaktik sistem içinde “öğretmen ve bilgi” üzerine yoğunlaşarak genetik öğretiminin içeriğini belirlemeyi amaçlamaktadır.Bu durum tespit çalışmasında iki farklı öğretmen çalışma grubunu oluşturmaktadır. Durum çalışmalarında önemli yer tutan veri kaynaklarından gözlem, görüşme ve doküman inceleme kullanılmış olup nitel veri analizi ile değerlendirilmiştir. Çalışmanın sonucunda; OKS sınavında başarı oranı yüksek olan okulda görev yapan öğretmenin genetik ile ilgili olan ders içeriğinin oluşturulmasında OKS sınavının etkisinin daha fazla olduğu bulunmuştur. Diğer taraftan OKS sınavı başarı oranı düşük olan okulda çalışan öğretmenin genetik ile ilgili derslerinin içeriğinin oluşturulmasında ders programlarının etkisinin daha fazla olduğu ortaya çıkarılmıştır.

Didactic transposition is involved with the processes that go to the definition of knowledge to be taught at a certain period. Therefore, it is in the form of historical, epistemological and sociological study of knowledge and it investigates the activities that realize the transposition of scientific knowledge to the form of learned knowledge by learner. This Didactic Transposition was described as “the whole transpositions that a knowledge undergo till it becomes a learned knowledge” by Chevallard (1985). This investigation aims to define the content of teaching genetics at the level of 8th class in primary education by focusing on ‘teacher and knowledge’ within didactic system. In another words, it aims to understand the role of teachers and curricula in composing of genetics teaching at the level of primary education. As an internal didactic transposition study, investigation has been carried out to discover the concepts that teachers have concerning genetics. In the assessment of situation study made with teachers who compose study group, an answer has been sought to following question: “What kind of relationship is there between genetics concept that teachers have and the content of relevant curricula?” The sentence of “Teachers prepare the content under the influence of curricula and/or HSE exam (The High School Entrance Examination) while planning or presenting concepts concerning genetics as subject content” has been determined as hypothesis. In the study, case study (sample event) from qualitative research methods and “integrated multiple case patterns” from case study has been used with the aim of investigation of data in a more detailed and deeper way. Because analysis unit is two teachers who work at two different Science and Technology High School and the level of successful of schools has been considered. While determining the study group, sampling excessive and repugnant case method from intentional sampling method has been selected to use. At the process of collecting data, the validation of structure has been increased by using more than one type of data. All details concerning collecting, assessing and reaching to the data have been explained in relevant parts within investigation in order to increase the internal validation and reliability. In the study, all teachers who work at the schools that were selected according to their schools’ level of success in the 2004-2005 term HSE exam in Kadikoy, Istanbul, were interviewed and two groups of teachers for suitable for study have been selected. The school at which T1 works as teacher is the most successful school according to HSE exam successful rate, T1 who has been teacher for 30 years graduated from a 3-year Education Institute. T1 gives Science and Technology courses in a fully-equipped laboratory. The school at where T2 works as a teacher is one of the lower school in Kadikoy according to HSE exam results. T2 who has been a teacher for 17 years is graduated from a 3-year Education Institute and gives courses at class. The techniques of document examination, observation and interview have been used in the study. Data has been examined in two groups in study. In order to detect knowledge to be taught, daily plans, teacher survey and interview that are first data group have been used. For knowledge that has already been taught, observation and teachers written exam questions that are second data group have been used. In this study, basically course have been followed and all data was collected during these observations. The first week that each teacher has started to Genetics unit and explained the parts concerning DNA and RNA was attended by researcher and researcher has used participant observation from the types of unstructured studies from observation techniques (Yildirim and Simsek, 2003). During these followed courses, courses were recorded with a recorder after getting necessary permits. The main titles of courses that researcher has followed is given at table 2. In order to analysis data, assessment forms that are given at appendix have been used. In the genetics unit of T1, it has been seen that concepts that T1 uses contains more variety and they have an upper level of formation at certain points. From these perspectives, it could be argued that T1 is under the influence of HSE rather than curricula. When all results are assessed as a whole, T1, even he/she has been under the influence of curricula, cares the success at HSE exam and shows this while preparing subject content and presenting it. On the other hand, T2 is under the influence of curricula while preparing exam question and planning the course. But, when all findings are considered, although it is on the top of level of course books and programs in terms of concepts’ variety and level of their formation, the influence of curricula has been seen more intensely. According to this, it has been seen that the individual relation of teacher who works at the school where the rate of success is higher, to concerning courses’ content is convenient to institutional relationship of HSE exam and the individual relation of teacher who works at the school where the rate of success is lower, to concerning course content is convenient to institutional relationship of curricula and course books. At the end of study, it has been suggested that under any condition curricula should be prepared in a way that they are able to be used in the same way in all schools; that the content of curricula and the content of exam programs should be parallel so that the worry for success in exams such as HSE should not affect the teachers to change course content; that teachers’ conditions during course should be improved and created equal conditions for schools and particularly Science and Technology courses should be taught in laboratories at every school; that authorized people and institutions should pay more attention at control mechanisms of internal class exercises of teachers and programs by considering these results with the reason of that it has been exposed that exams such as HSE has big importance on teachers to determine course content and therefore causes opportunity inequality.
Evaluation of teacher's knowledge with "didactic transpositiontheory" approach on the genetics unitin primary scienceand technology course
Keywords: Matematik; Eğitim, Eğitim Araştırmaları; Eğitim, Özel